Boronic acid-modified cell-penetrating peptide exhibits superior performance over natural TAT peptide - Ghosh, Pritam (Frontiers in Chemical Biology, 2025)
This study explores an enhancement to a cell-penetrating peptide (CPP), specifically cyclic deca arginine (cR10), by modifying it with boronic acid to improve the delivery efficiency of ubiquitin (Ub), an essential protein that plays various roles in cellular functions. The hypothesis is that adding boronic acid could boost cellular uptake through glycan-boronic acid interactions. This research assesses how the boronic acid-modified cR10 compares to TAT, a natural CPP derived from the HIV-1 transactivator of transcription, in delivering Ub into cells. Experiments with U2OS cells indicated that the boronic acid-linked cR10Ub cargo achieved a fourfold increase in cellular uptake compared to the TAT-Ub conjugate. The findings from this study could contribute to developing new approaches for enhancing protein delivery methods relevant to biomedical research and therapeutic applications.